Swimming Exercise Changes Hemodynamic Responses Evoked by Blockade of Excitatory Amino Receptors in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Ogihara, Cristiana A.; Schoorlemmer, Gerhardus H. M.; Lazari, Maria de Fatima M.; Giannocco, Gisele; Lopes, Oswaldo U.; Colombari, Eduardo [UNESP]; Sato, Monica A. (Hindawi Publishing Corporation, 2014)
Exercise training reduces sympathetic activity in hypertensive humans and rats. We hypothesized that the swimming exercisewould change the neurotransmission in the rostral ventrolateral medulla (RVLM), a key region involved in sympathetic outflow, and hemodynamic control in spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats. Bilateral injections of kynurenic acid (KYN) were carried out in the RVLM in sedentary- (S-) or exercised- (E-) SHR and WKY rats submitted to swimming for 6 weeks. Rats were alpha-chloralose anesthetized and artificially ventilated, with Doppler flow probes around the lower abdominal aorta and superior mesenteric artery. Injections into the RVLM were made before and after i.v. L-NAME (nitric oxide synthase, NOS, inhibitor). Injections of KYN into the RVLM elicited a major vasodilation in the hindlimbmore than in the mesenteric artery in E-SHR compared to S-SHR, but similar decrease in arterial pressure was observed in both groups. Injections of KYN into the RVLM after i.v. L-NAME attenuated the hindlimb vasodilation evoked by KYN and increased the mesenteric vasodilation in ESHR. Swimming exercise can enhance the hindlimb vasodilation mediated by peripheral NO release, reducing the activation of neurons with EAA receptors in the RVLM in SHR.